2001
DOI: 10.1111/j.1939-165x.2001.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Antioxidant Changes in Plasma and Erythrocytes of Pentathlon Horses Before and After Exercise

Abstract: Physical exercise in the horse induces a series of normal physiological and biochemical adaptations. Increasing metabolism and oxygen uptake may induce oxidative stress in various organs. The aim of this study was to examine exercise-induced changes in some plasma and RBC biochemical and antioxidant variables in pentathlon horses. Blood samples were taken from 14 horses before, immediately after, and 24 hours after competing in two 1-minute runs of intense exercise over jumps. The peak intensity periods were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 22 publications
11
40
2
4
Order By: Relevance
“…Williams et al (2004) found that GSHPx activity in mU/mg of TP was significantly increased (P < 0.05) but no change was found in the concentration of α-tocopherol, which was adjusted to albumin due to changes in body fluid redistribution during endurance exercise. Similarly to our findings, when expressed as units per g of TP, Balogh et al (2001) found unchanged activity of GSHPx and SOD (both in U/g of TP), and unaffected index of lipid peroxidation (in mmol/g of TP) in pentathlon competition finishing horses, but the index of lipid peroxidation was decreased after 24 h of rest.…”
Section: Enzymatic Metabolismsupporting
confidence: 68%
“…Williams et al (2004) found that GSHPx activity in mU/mg of TP was significantly increased (P < 0.05) but no change was found in the concentration of α-tocopherol, which was adjusted to albumin due to changes in body fluid redistribution during endurance exercise. Similarly to our findings, when expressed as units per g of TP, Balogh et al (2001) found unchanged activity of GSHPx and SOD (both in U/g of TP), and unaffected index of lipid peroxidation (in mmol/g of TP) in pentathlon competition finishing horses, but the index of lipid peroxidation was decreased after 24 h of rest.…”
Section: Enzymatic Metabolismsupporting
confidence: 68%
“…And the capacity in plasma is related to production or intake of antioxidants. Hence, it monitors the action potential to increased or normal status of reactive oxygen species (Miller et al 1993;Lantos et al 1997;Ghiselli et al 2000;Balogh et al 2001). This study reported that LMD treatments at low concentrations (5, 10, 20 and 40 lg/ml) caused significant increase of TAC levels, while TOS levels were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that activities of various enzymes, particularly of creatine kinase and glutamate pyruvate transaminases, increase following muscle damage o r strenuous muscular exercise (Balogh et al, 2001).…”
Section: Resultsmentioning
confidence: 99%